Modeling of the Core and Analysis of the Operation of a Nuclear Microreactor (2023)
This research focuses on a detailed analysis of the operation and modeling of the core of a prototype nuclear microreactor with characteristics similar to Westinghouse’s eVinci nuclear microreactor. To achieve this, firstly, the RootT M software is employed to adapt the energy spectrum under which the 241Am-Be source operates. Secondly, the Geant4TM simulation tool is used, where, starting from the configuration of a cylinder embedded in a box, the unit cell is established to obtain a trapezoidal geometry as a geometric component of the hexagonal core of the microreactor. Additionally, the essential parameters of the functions enabling the reproduction of data from a 241Am-Be source are presented in the results, playing a crucial role in initiating nuclear fissions in the uranium dioxide UO2 fuel rods. Finally, the appropriate dimensions of the various components of the core are established, including the fuel rods, neutron moderators, and control drums located within the microreactor.